Efektivitas Pelatihan Berbasis Peer Teaching: Pendampingan Penguasaan Tata Cara Perawatan Jenazah pada Kelompok PKK - Fitri, Fitri; Hasbi, Muhammad; Rifaldi, Muhammad; Jumartang, Jumartang; Nurjayanti, Nisa; Asmidin, Muhammad; Kadir, Alhabib; Amaliyah, Nurul; Upi, Besse (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Lack of understanding and practical skills regarding the procedures for handling corpses according to Islamic law remains a problem in Ganra District, Soppeng Regency. Heavy reliance on local religious leaders often hinders the prompt and appropriate handling of corpses. This Community Service (PkM) activity aims to improve the theoretical understanding and psychomotor skills of Family Welfare Movement (PKK) members in corpse handling through a participatory approach. The PkM implementation used a peer-teaching training method, which included a pre-test, material presentation, expert demonstration, guided independent practice, and a post-test. Evaluation results showed a significant increase in participant capacity, with the average score jumping from 43.75 (low category) to 86.25 (very good category). The highest increase occurred in the technical aspect of shrouding, with a 123% increase. In addition to the numerical results, this method successfully transformed participants' psychological state from fear and doubt to confidence and independence through the use of egalitarian and familiar language. This activity contributed to the formation of an ecosystem of collective responsibility at the hamlet level. Skilled PKK cadres now provide an alternative solution for fulfilling fardu kifayah obligations, while reducing absolute dependence on senior religious figures in Ganra District.